2020
DOI: 10.9734/jpri/2020/v32i1730669
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Antimicrobial Efficacy of Octenidine Dihydrochloride with Contemporary Root Canal Disinfectants: A Systematic Review

Abstract: Octenidine is a cationic disinfectant that has been tested for its wide range of antibacterial efficacy and biocompatibility. It finds its application in the medical field as an antiseptic for wounds and mucous membranes. The present systematic review aims to compare the antimicrobial efficacy of Octenidine Dihydrochloride with various root canal irrigants and medicaments. An electronic search strategy was planned to search the database of PUBMED CENTRAL and MEDLINE using the search terms alone and in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Root canal disinfectants were widely used to eliminate the microbes in root canals [ 7 ]. However, clinical root canal disinfectants, such as chlorhexidine acetate, cresol and formaldehyde solution, calcium hydroxide, possess inherent defects that bring risks to patients and affect their long-term applications [ 8 ]. Nowadays, nanomaterials have been widely used in EIs to inhibit bacteria in the root canals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Root canal disinfectants were widely used to eliminate the microbes in root canals [ 7 ]. However, clinical root canal disinfectants, such as chlorhexidine acetate, cresol and formaldehyde solution, calcium hydroxide, possess inherent defects that bring risks to patients and affect their long-term applications [ 8 ]. Nowadays, nanomaterials have been widely used in EIs to inhibit bacteria in the root canals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of octenidine as an antiseptic agent has been widely studied. Its main uses include body washes for disinfection and prevention of (especially nosocomial) infections; 30 disinfection of surfaces and surgical material; 31 wound healing via impregnated dressings and bandage; 32 its use in dentistry as mouthwashes 33 for the treatment of gingivitis and other oral infections; 34 and its application for the treatment of vaginal infections. 35 However, no studies have been found on its use as a topical antiseptic to control overgrowth of S. aureus in skin with eczema or with an atopic tendency to prevent and reduce skin symptoms.…”
Section: Discussionmentioning
confidence: 99%